Integrasi Etika Halalan Thayyiban dalam Mendukung Tujuan Pembangunan Berkelanjutan dalam Fesyen Halal Indonesia - Baitul Hamdi; Agus Suaidi Hasan (Journal of Principles Management and Business, 2026)
Global industrial development has seen progress in environmental friendliness. The industry is required to increase global competition while continuing to prioritize sustainability. This situation has pushed the halal market to adopt an alternative ethical approach. Indonesia, the world's leading modest fashion producer, faces a problem with textile waste, which reaches 2.3 tons annually. This article aims to analyze halal ethics and thayyib (goodness of fit) in supporting environmental sustainability (hifdzul bi'ah) in the halal fashion sector. This study uses a descriptive qualitative approach through a literature review and content analysis. The data used include secondary data from SGIE and MEKSI reports, articles, books, and digital information. The results show a shift in the ethical paradigm in halal standardization, which goes beyond the normative halal approach. This shift is driven by pioneering brands that consistently implement the 5R principles of sharia. The internalization of environmentally friendly criteria in halal certification regulations has also been initiated through MEKSI 2025-2029. A shift in values and a holistic approach to advancing the halal fashion industry while remaining environmentally friendly are crucial and align with achieving SDGs 8,9, 12, 13, and 15.  This study has several limitations due to its focus on a qualitative descriptive approach and specific brands. Therefore, empirical testing is needed to confirm the results.